Level of Satisfaction and Confidence After Using Virtual Reality Simulation of Wound Care Skills in Nursing Students - Regita Suryadi, Yasmina Dwi; Komariah, Maria; Eriyani, Theresia (Universitas Padjadjaran, 2024)
Virtual laboratory practice using virtual reality provides conveniences and increases learning outcomes, beside physical laboratories requires expensive costs, ineffective and efficient, and limited space causes a decrease in learning levels and impacted to satisfaction and confidence. This study aims to identify satisfaction and confidence of nursing students in learning using Virtual Reality of Wound Care Skills. The research design using descriptive quantitative. In this study, 56 nursing students used as samples using quota sampling technique. Student Satisfaction and Self-Confidence in Learning Scale (SCSL) is the instrument used in this study. Meanwhile, data analysis was performed using IBM SPSS software version 26 with univariate analysis method and presented in the form of distribution frequency tables, yield percentages, mean, and deviations standard. This study shows that students are very satisfied (M = 4.400; SD = 0.670) and very confident (M = 4.357; SD = 0.622) in learning using Virtual Reality of Wound Care Skills. Results obtained from the use of virtual reality learning simulations on student satisfaction and confidence obtained high scores. Therefore, this learning method can used as an alternative to learning and support student skills and knowledge in another nursing skills.